Identifying the best reference gene for RT-qPCR analyses of the three-dimensional osteogenic differentiation of human induced pluripotent stem cells - Masakazu Okamoto; Yusuke Inagaki; Kensuke Okamura; Yoshinobu Uchihara; Kenichiro Saito; Akihito Kawai; Munehiro Ogawa; Akira Kido; Eiichiro Mori; Yasuhito Tanaka (Bone Reports)
Reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) is an essential tool for gene expression analysis; choosing appropriate reference genes for normalization is crucial to ensure data reliability. However, most studies on osteogenic differentiation have had limited success in identifying optimal reference genes. To the best of our knowledge, no optimal reference genes in three-dimensional (3D) osteogenic differentiation culture experiments using human induced pluripotent stem cells (hiPSCs) have been identified. In this study, we aimed to identify stable reference genes that could be used for normalization in gene expression analyses during the 3D osteogenic differentiation of hiPSCs using an atelocollagen sponge as a scaffold. Four algorithms—ΔCt, BestKeeper, NormFinder, and geNorm—were used to evaluate the stability of 14 candidate reference genes. Genes encoding TATA box-binding protein, hypoxanthine phosphoribosyltransferase 1, and 14–3-3 protein zeta polypeptide were identified as the most stable reference genes. In comparison, conventionally used reference genes (beta-2 microglobulin and beta-actin genes) ranked among those with low stability. We also demonstrated the successful 3D osteogenic differentiation of hiPSCs on atelocollagen sponge. Our findings provide valuable insights for reference gene selection and bone tissue regeneration from hiPSCs, which could improve the treatment prospects for bone defects and other similar conditions in regenerative medicine.